Poor Adherence to Self-Applied Topical Drug Treatment Is a Common Source of Low Lesion Clearance in Patients with Actinic Keratosis—A Cross-Sectional Study - Koch, Elias; Steeb, Theresa; Bender-Säbelkampf, Sophia; Busch, Dorothee; Feustel, Janina; Kaufmann, Matthias; Maronna, Andreas; Meder, Christine; Ronicke, Moritz; Toussaint, Frédéric; Wellein, Hedwig; Berking, Carola; et al. (Journal of Clinical Medicine, 2023)
Background: Many treatments for actinic keratosis (AK) have been proven efficient in clinical trials. However, patients with AK may still experience unsatisfactory therapeutic outcomes in clinical practice. Objectives: To investigate patient adherence to self-applied topical interventions for AK and to explore factors associated with adherence in a real-world setting. Methods: A cross-sectional study was conducted. Patients presenting with AK were asked to complete a self-administered questionnaire about their last topical AK treatment. Results: A total of 113 patients participated with a median age of 78.5 years (range 58–94). Fifty-four patients (47.8%) received topical diclofenac, ten (8.8%) imiquimod, nine (8%) 5-fluorouracil, nine (8%) 5-fluorouracil plus salicylic acid, and eight (7.1%) photodynamic therapy. The non-adherence rate was 46.9% (n = 53), and only 30.9% (n = 35) used the topical treatments according to the summary of product characteristics (SmPC). These subgroups were compared. Patients of the non-compliant group were significantly less informed about the application time of the specific topical intervention (p = 0.002) and adjusted the timeframe (p < 0.001) and application frequency of the therapy (p = 0.02) independently of their physician. Conversely, patients reporting a sufficient pre-treatment consultation (p = 0.019) generally complied with the SmPC compliance application. Conclusions: A thorough pre-treatment consultation can help to increase treatment adherence and ensure lesion clearance.
CRIS-Team Scopus Importer:2023-06-30
Keywords: actinic keratosis; adherence; compliance; consultation; topical treatment